Design of capacitive sensing chopper amplifier used in artificial nose detection system - Tuševski, Ajda (Informacije MIDEM, 2024)
In this paper, we present the theoretical background and design procedure of a fully differentiated precision charge amplifier that can be used to detect small capacitive changes in an artificial nose detection system (ANose). We will show that with appropriate topology and optimization of circuit parameters, we can reduce 1/f noise and the offset and thus improve the sensitivity while keeping the power consumption at an acceptable level. Since the rate of capacitive changes due to adsorption/desorption is slow, a well-known technique such as chopping and autozeroing is used in a new way and described in the paper. The advantages and disadvantages of the proposed techniques are described. A combination of these two techniques in a single topology and new capacitive sensor ports are used to improve the detection sensitivity. Ideally, a sensitivity of 3 zF/?$\sqrt$?Hz can be achieved, but it could be slightly worse due to various non-idealities not considered.
Keywords: artificial nose; capacitive sensors; diferencialni kapacitivni senzorji; fully differential chopper amplifier; popolnoma diferencialen sekalni ojačevalnik; ripple reduction loop (RRL); RRL 3; umetni nos